Adherence to antiretroviral treatment and associated factors in people living with HIV/AIDS in Quindío, Colombia (2017)
Introduction: HIV/AIDS is a chronic disease; therefore, recognizing which factors favor adherence to antiretroviral treatment is necessary.Objective: To determine the association between adherence to antiretroviral treatment and depression, anxiety, perception of social support and sociodemographic variables in people living with HIV/AIDS in Quindío, Colombia.Materials and methods: An observational, cross-sectional study was performed in an intentional sample of 70 adults, who were applied the Morisky-Green questionnaire, the Beck Depression Inventory, the Beck Anxiety Inventory, the Medical Outcomes Study (MOS) Social Support Survey, and a sociodemographic survey. Univariate and bivariate analyzes were performed by calculating the odds ratio to determine association (p0.05).Results: 57.1% of the participants reported low adherence to treatment, 30% had moderate or severe depressive symptoms, 71.4% scored minimal or mild anxiety levels, and 77.1% had a low perception of social support. A statistical association between depression (high levels tripled the risk of non-adherence) and self-report on how treatment is followed (excellent or good self-report increased by five times the probability of adherence) was found.Conclusion: Depression and self-report on compliance were associated with adherence to antiretroviral therapy. A comprehensive study on the perception of social support and cognitive variables, such as self-efficacy and risk perception, is highly recommended for people living with HIV/AIDS.